Translation Theory: Where Are We Going? - Bell, Roger (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1987)
AbstractIn this paper it is asserted that, despite recent movements in continental translation theory (see Wilss 1982 : 59, for an admirable summary of the situation), the essential orientation of translation theory, in the English-speaking world in particular, is still towards the evaluation of translation as product (i.e. as the translated text) and, by means of such evaluation, towards the discovery or creation of a set of normative maxims for the production of the ideal translation.What is proposed is a shift of focus away from the translation as an artifact - a product - towards translating as process i. e. an investigation of the psycholinguistic mechanisms of decoding and encoding in the context of bi- rather than monolingual information exchange. The paper concludes with some tentative hints at parts of the decoding elements of a model of translating which, it is hoped, will help to orient translators and teachers towards the means by which texts are transferred from language to language and from speech community to speech community ; a process which is universally recognized as a sine qua non for the improvement of international relations in a sadly divided world.